Design and Testing Games with Children - Abdulghani, Balsam (My University, 2021)
This thesis aims to introduce the different phases of preparation and testing games with children as players, and how the test results affect the game design. Children can play different roles in the user-centered design and the level of their involvements is based on role. The thesis goals were achieved through the involvement of children as testers and evaluators in three different tests carried out for the Pikkuli motion game. The Pikkuli motion game (branch and flapping) was developed by Turku Gamelab and SunInEye productions. To ensure the correctness and validation of data collected during the tests, a combination of eye tracking and think-aloud, interview and questionnaire, and observation methods were used. The data collected from eye tracking devices were analyzed using different algorithms. The results revealed some serious problems with the game balance of the Branch game. The results also revealed another problem in the user interface, where some icons were not clear enough to the testers. The results and recommendations were provided to the designer team to improve the gameplay design as well as the user interface design.
Keywords: Play, game, game design, child development, user testing, test with children, eye tracking, Pikkuli motion game